The Central Park five [videorecording (DVD)] - Burns, Ken, 1953-; Burns, Ken, 1953-; Burns, Ken, 1953-; McMahon, David, 1976-; McMahon, David, 1976-; McMahon, David, 1976-; Burns, Sarah, 1982-; Burns, Sarah, 1982-; Burns, Sarah, 1982- (PBS : Distributed by PBS Distribution, 2013)
Chronicles America's complicated perceptions of race and crime through the story of the "Central Park 5"--A group of minority teenagers wrongfully convicted and jailed for brutally raping a white woman in New York.